2005
DOI: 10.1248/bpb.28.2220
|View full text |Cite
|
Sign up to set email alerts
|

Curcuma longa Extract Protects against Gastric Ulcers by Blocking H2 Histamine Receptors

Abstract: Curcuma longa (C. longa), a common Indian dietary pigment and spice, has been used therapeutically in traditional folk medicine for a wide range of ailments, including wound healing, urinary tract infection, and liver ailments.1,2) Although evidence suggests that a C. longa extract also has considerable gastroprotective and antiulcerogenic effects, 3,4)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 20 publications
(16 reference statements)
3
40
0
1
Order By: Relevance
“…Another study about NSAID-induced gastric damage showed that curcumin can increase catalase and superoxide as well as nitric oxide levels in the gastric mucosa (6,25) . The beneficial effects of curcumin on gastritis can be created by the inhibition of gastric acid production due to inhibition of histamine receptors (14) . Another strength point of this study was comparison of the H. pylori eradication rates between triple therapy regimen plus curcumin and triple therapy regimen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study about NSAID-induced gastric damage showed that curcumin can increase catalase and superoxide as well as nitric oxide levels in the gastric mucosa (6,25) . The beneficial effects of curcumin on gastritis can be created by the inhibition of gastric acid production due to inhibition of histamine receptors (14) . Another strength point of this study was comparison of the H. pylori eradication rates between triple therapy regimen plus curcumin and triple therapy regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Packed cell lyses were prepared with distilled water in a ratio of 1:10 to measure the markers. Successful H. pylori eradication was defined as a negative 14 C-urea breath test result and a negative H. pylori stool antigen test result 4 weeks after discontinuation of therapy (22) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcuma longa, has been used in traditional remedy for a wide range of ailments, including wound healing, urinary tract infection, and liver ailments [10]. Although, curcumin has been defined as the most active component in C longa and has a considerable gastroprotective and antiulcerogenic effect, its antiulcer potential activity was recently confirmed and reviewed by our laboratory [11].…”
Section: Introductionmentioning
confidence: 99%
“…[64] Kim et al [65] discovered the defensive effect of turmeric ethanolic extract against gastric ulcers by blocking H2 histamine receptors (H2R) of male Sprague-Dawley (pylorus-ligated) rats. The effect of C. longa extract was compared to the properties of ranitidine.…”
Section: Dyspepsia and Gastric Ulcermentioning
confidence: 99%